Feasibility Analysis of Cocoa Rejuvenation in Jambewangi Village, Sempu District, Banyuwangi Regency - Arbian Ade Kharisma; Rena Yunita Rahman; Soetriono; Ariq Dewi Maharani; Gatot Subroto; Indah Ibanah (CV Edujavare Publishing, 2026)
Cocoa is one of the leading plantation commodities that plays an important role in the agricultural sector. Banyuwangi Regency is the largest cocoa-producing region in East Java Province, with the highest cocoa production concentrated in Sempu District. However, despite its high production, cocoa productivity in Sempu District remains relatively low compared to other districts within the regency. This low productivity is mainly attributed to the aging cocoa trees, which are more susceptible to pests and diseases, as well as inadequate crop management practices. One of the strategies to improve cocoa productivity is through rejuvenation. This study aimed to evaluate the financial and non-financial feasibility of cocoa rejuvenation. The research was purposively conducted in Jambewangi Village, Sempu District, Banyuwangi Regency. Both primary and secondary data were collected and analyzed using Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP) analyses. The results indicated that the replanting method generated a Net Present Value (NPV) of IDR 83,671,483, a Net B/C ratio of 2.88, an Internal Rate of Return (IRR) of 20.78%, and a Payback Period (PP) of 6.3 years at a discount rate of 6% over a 20-year production period. Meanwhile, rejuvenation through side grafting and top grafting produced an NPV of IDR 52,858,871, a Net B/C ratio of 2.43, an IRR of 34.31%, and a Payback Period of 3.2 years at the same discount rate over a 7-year production period. From a non-financial perspective, cocoa rejuvenation in Jambewangi Village was also found to be feasible, as it provides significant benefits to cocoa farmers and the surrounding community. Therefore, cocoa rejuvenation can be considered a viable strategy to improve cocoa productivity and support the long-term sustainability of cocoa farming.